2013
DOI: 10.1016/j.exphem.2013.04.002
|View full text |Cite
|
Sign up to set email alerts
|

A model of glucose-6-phosphate dehydrogenase deficiency in the zebrafish

Abstract: Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most common genetic defect and enzymopathy worldwide, affecting approximately 400 million people and causing acute hemolysis in persons exposed to prooxidant compounds such as menthol, naphthalene, anti-malarial drugs, and fava beans. Mouse models have not been useful because of a lack of significant response to oxidative challenge. We turned to zebrafish (Danrio rerio) embryos, which develop ex utero and are transparent, allowing visualization of hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 32 publications
2
33
0
Order By: Relevance
“…The significant increase in expression of these NADPH-generating enzymes at 72 hpf corresponds to the developmental timepoint at which zebrafish embryos can maintain a stable redox environment that allows for the continued maintenance of a large ratio of reduced GSH to oxidized GSH (GSSG) (Timme-Laragy et al, 2013). Interestingly, a previous zebrafsih study has demonstrated a reduction of red blood cell staining and an increase in oxidative stress in 72 hpf G6pd morphants exposed to the pro-oxidant 1-naphthol (Patrinostro et al, 2013), highlighting the important role of NADPH maintenance in protection against oxidative stress. Furthermore, the cellular redox environment of early embryos and the expression profiles of many of the NADPH-producing enzymes raise some interesting questions regarding tissue-specific production levels of NADPH during early zebrafish development.…”
Section: Discussionmentioning
confidence: 96%
“…The significant increase in expression of these NADPH-generating enzymes at 72 hpf corresponds to the developmental timepoint at which zebrafish embryos can maintain a stable redox environment that allows for the continued maintenance of a large ratio of reduced GSH to oxidized GSH (GSSG) (Timme-Laragy et al, 2013). Interestingly, a previous zebrafsih study has demonstrated a reduction of red blood cell staining and an increase in oxidative stress in 72 hpf G6pd morphants exposed to the pro-oxidant 1-naphthol (Patrinostro et al, 2013), highlighting the important role of NADPH maintenance in protection against oxidative stress. Furthermore, the cellular redox environment of early embryos and the expression profiles of many of the NADPH-producing enzymes raise some interesting questions regarding tissue-specific production levels of NADPH during early zebrafish development.…”
Section: Discussionmentioning
confidence: 96%
“…Researchers have been trying to identify factors that increase the risk of AD such as aerobic exercise, pesticides, elevated serum cholesterol concentrations, carotenoids, abdominal obesity, and exposure to aluminum, head injury, malnutrition, immune system dysfunctions, and infectious agents [46][47][48][49][50][51]. G6PD deficiency is the most common genetic defect and enzymopathy worldwide, affecting approximately 400 million people and causing acute hemolysis in patients exposed to oxidative compounds such as menthol, naphthalene, antimalarial drugs, and fava beans [52]. G6PD is the first and the rate-limiting enzyme of the pentose phosphate pathway (PPP).…”
Section: Novel Targets For Alzheimer's Diseasementioning
confidence: 99%
“…Prior zebrafish models of G6PD deficiency develop pericardial edema in response to oxidative challenge and resulting anemia [16]. To evaluate for heart malformations and pericardial edema secondary to G6PD deficiency, F3 homozygous Tg(zgata1:g6pd M1315-1443 -egfp) transgenic zebrafish line were compared with wildtype.…”
Section: G6pd Activity In Tg(zgata1:g6pd M1315-1443 -Egfp) Transgenicmentioning
confidence: 99%
“…Patrinostro et al [16] established a zebrafish models of G6PD deficiency using morpholinos targeting the 5-prime exons of g6pd, but the model is limited to transient knockdown of g6pd.…”
Section: Introductionmentioning
confidence: 99%